Development and analysis of recombinant fluorescent probes for use in live cell imaging of filamentous fungi - Altenbach, Kirsten (The University of Edinburgh, 2010)
The molecular cloning and subsequent engineering of the green fluorescent protein (GFP) of the jellyfish Aequoria victoria allowed a novel approach to the investigation of cell signalling. GFP and its mutants can now not only be used to target specific organelles in living cells but also function as a basis for a variety of sensors for biologically important ions and molecular interactions. GFP-based Ca2+- sensors have been successfully used for studies in mammalian and plant cells. In filamentous fungi, however, they have not yet been reported to work. Since only little is known about calcium signalling in filamentous fungi, this project aimed to improve existing GFP-based Ca2+- sensors by exchanging the original fluorophores for improved versions and expressing those in the filamentous fungus Aspergillus niger. During this project, the donor and acceptor fluorophores of 3 existing Ca2+-FRETprobes based on cameleons and troponin C-sensors, have been changed, 2 novel positive FRET controls have been designed and these , as well as donor and acceptor fluorophores alone, have been expressed in the filamentous fungus Aspergillus niger. The probes were assessed using different imaging techniques, such as conventional confocal laser scanning microscopy (CLSM), fluorescence lifetime imaging microscopy (FLIM) and spectral imaging using a Leica TSC SP5 confocal and IRIS, a novel spectral imaging device designed at Heriot Watt University. Problems were encountered that prevented FRET analysis using CLSM and IRIS. These were due mainly to the difference in expression level of the constructs and the distribution of the emission bandpasses of the IRIS system. Analysis of the spectral data obtained on the Leica confocal system and analysis of the FLIM results, however, revealed significant differences between the donor only and the positive FRET controls. Spectra of the positive FRET controls and the Ca2+-sensitive probes showed emission peaks of both the donor and the acceptor fluorophores upon excitation of the donor fluorophore alone while analysis of the FLIM results revealed an additional decay component in the positive FRET controls. Both results are very strong indicators that we can detect FRET in living hyphae of Aspergillus niger transformed with the probes designed during this project.
Keywords: live cell imaging; aspergillus niger; FRET; FLIM; fluorescent probes